Gendering Piety, Justice and Violence: On the Aesthetics of Self-Killing in Han-Chinese, Naxi and Lahu Cultures (from the Late-Ming to Mid-20th Century) - Previato, Tommaso (Annali di Ca' Foscari: Serie Orientale, 2022)
Self-killing in late imperial and modern China called into play gender disparities, and secular and religious morals often at odds with each other. Scholarship has long focused on Confucian virtue ethics that led young widows to follow their husband to death, or take a chastity vow and disfigure themselves to avoid rape, but little effort has been made to examine suicide practices cross-culturally. This paper compares such practices among Han women from the southeast coast and indigenous Naxi and Lahu women of upland Yunnan, throwing light on the aesthetics behind their struggles for justice, free-choice marriage and beliefs in posthumous love.
Created from Fastlane, Scopus look-up
Keywords: Afterlife beliefs; Filiality; Gender-role distinctions; Self-inflicted violence; Suicide